"The Other Side of the Brocade": Translating Fashion Blogs and Data Mining. (3rd April 2022) - Shen, Zheng
Abstract: T his article takes both a literal and figurative approach to dress and translation. With the breakthrough of social media, microblogging has become an influential medium for marketing fashion brands and products online. The article reports on the findings of a three-year research project that studied ten Irish and ten Chinese fashion microblogging influencers' blogs using Text Mining and Netnography. The author first designed a digital tool for data mining that allows the simultaneous translation of Chinese microblogs into English and vice-versa, also enabling visualizations of most frequent words through word clouds, and displaying the context in which they were used through collocations. These linguistic and visual translations became the basis to elaborate a typology of blogging strategies. Second, using the metaphor of translation as "the other side of a brocade, " the author compares the strategies followed by the Chinese and the Irish micro-bloggers as if they were the two sides of a single work, given that they are all arranged around the same list of categories. The article thus provides empirical and visual evidence on the use of translation to understand fashion blogging and the values there expressed, across cultures.